Merriam-Webster's elementary dictionary. - Merriam-Webster, Inc. (Springfield, Mass. : Merriam-Webster, 2005)
A dictionary for students ages eight to twelve with meanings and uses given for more than 32,000 words. Includes explanatory introductory material.
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries